Solar Degradation of Formic Acid: Temperature Effects on the Photo-Fenton Reaction - Farias, Jorgelina (2007)
The effect of the reaction temperature on the degradation rate of formic acid, using the Fenton and photo- Fenton processes, is investigated. First, for both reactions, a stirred tank laboratory photoreactor irradiated from the bottom was used to evaluate the kinetic parameters between 298 and 328 K. Afterward, the proposed kinetic model was used to predict the conversion of the organic pollutant in a flat-plate solar photoreactor. The previously reported radiation field and mass balances have been used to compute the formic acid and hydrogen peroxide concentrations as a function of time in the solar reactor. Theoretical and experimental results show that UV solar radiation improves the effectiveness of the Fenton process. At lower temperatures, the pollutant conversion enhancement is significant, but this effect is less important at higher temperatures. For instance, experimental conversion enhancements after 20 min are 186.0, 74.0, and 7.4% for 298, 313, and 328 K, respectively.